Seksualitas, Keperjakaan, dan Disabilitas: Analisis terhadap Film "Why Do You Love Me" - Febrina, Dhea (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
Some research indicates that sexuality and disability are two taboo concepts that are rarely combined. Individuals with disabilities are often portrayed as asexual or hypersexual. The film Why Do You Love Me (2023) attempts to break these stereotypes and depicts sexuality as a symbol of empowerment through the story of three friends with disabilities embarking on a journey to lose their virginity. This study aims to analyze how the film portrays sexuality and virginity of individuals with disabilities. Using a qualitative approach, the research uses critical disability theory and multimodal discourse analysis with critical standpoint to identify dialogues and scenes in the film related to dominant ideologies and accuracy in disability representation. Despite raising a unique theme and diversifying the representation of individuals with disabilities in mainstream media, the results reveal that the practice of “cripping up” perpetuates dominant perspectives and diction in the film’s lexical and visual elements. It uses sexuality and virginity as selling points to determine the social status of men with disabilities amidst societal norms of masculinity. Humor and cinematographic techniques still employ ableist discourses, suggesting the need of men with disabilities for accommodation from the dominant group. Insights for altering cinematic representations of disabilities are explored.